FitForLife: study protocol for a randomized controlled trial - Forsell, Yvonne (Trials, 2015)
BACKGROUND: Psychosis is a serious mental illness that typically emerges during early adulthood. The disorder is characterized by inactivity, cognitive deficits and the need for ongoing support. Regular exercise has mood enhancing and anxiolytic effects that could benefit this patient group. To date, few studies have examined the effects of prescribed exercise on autonomy, health and cognitive functioning in psychosis. METHODS/DESIGN: This is a single-center, randomized controlled trial (RCT) with a 3-month follow-up. Usual care plus a 12-week supervised exercise program will be compared to usual outpatient care alone. The primary outcome will be patient autonomy measured by the Camberwell Assessment of Need (CAN) schedule – clinician rated. Secondary outcomes include cardiovascular risk factors, cognitive functioning, substance abuse, body awareness, depression and mood state. Changes in inflammatory markers and microbiotica will be explored. The feasibility of using patients as exercise trainers will also be assessed. DISCUSSION: The treatment potential for exercise in psychosis is large because most individuals with the disorder are young and inactive. The study is one of the first to comprehensively assess the effects of regular exercise in young adults with psychosis. Sessions will be closely supervised and adjusted to meet patient needs. Both the feasibility and treatment effects of exercise interventions in psychosis will be discussed. TRIAL REGISTRATION: German Clinical Trials Register DRKS00008991 7 August 2015.